Allatini Dormitory, 3 Paraskevopoulou Street: Despair and Hope in Salonika after the Shoah - Benveniste, Henriette-Rika (Historein, 2019)
The Jews who lived in Salonika in 1945 and who survived the extermination will of the Nazis form an exception. The article explores the life of camp survivors returning to their home city. Practical relief was mainly organised by the Jewish community. Besides mourning for the loss of entire families, economic hardship, scarcity of material resources and political insecurity were the main characteristics of those years. The article focuses on the life in a building belonging to the Jewish community, the former Allatini Orphanage, which became a “dormitory” to shelter about 60 homeless Jews, mostly camp survivors. It examines the extreme poverty, the demands, the sociability and the migration choices of men and women who depended on the community’s care. Their voices, their mourning and their thirst for a new life can be heard piercing the paperwork of the bureaucracy of a welfare system and will help us reconstruct a difficult return to “normality”.